2023
DOI: 10.1523/jneurosci.0478-23.2023
|View full text |Cite
|
Sign up to set email alerts
|

Neuromechanical Strategies for Obstacle Negotiation during Overground Locomotion following Incomplete Spinal Cord Injury in Adult Cats

Abstract: Following incomplete spinal cord injury in animals, including humans, substantial locomotor recovery can occur. However, functional aspects of locomotion, such as negotiating obstacles remains challenging. We collected kinematic and electromyography data in ten adult cats (5 males, 5 females) before and at weeks 1-2 and 7-8 after a lateral mid-thoracic hemisection on the right side of the cord while they negotiated obstacles of three different heights. Intact cats always cleared obstacles without contact. At w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 88 publications
0
5
0
Order By: Relevance
“…While we identified that the hold region was an important state space feature in governing the duration of extensor burst during air stepping, we acknowledge that the utility of this feature may not be apparent or implemented across all behaviors. Behaviors that are dominated by flexor-muscle activity or require more variation in the duration of the swing phase (e.g., obstacle avoidance, (Lecomte et al, 2023)) may require different mechanisms to generate that type of motor output variability that we did not observe in the spinal cat during air-stepping. Additionally, the extension bias we observed may also be attributed in part due to the experimental conditions (i.e., spinalized animal, clonidine-induced, air stepping with no ground reaction forces).…”
Section: Discussionmentioning
confidence: 66%
“…While we identified that the hold region was an important state space feature in governing the duration of extensor burst during air stepping, we acknowledge that the utility of this feature may not be apparent or implemented across all behaviors. Behaviors that are dominated by flexor-muscle activity or require more variation in the duration of the swing phase (e.g., obstacle avoidance, (Lecomte et al, 2023)) may require different mechanisms to generate that type of motor output variability that we did not observe in the spinal cat during air-stepping. Additionally, the extension bias we observed may also be attributed in part due to the experimental conditions (i.e., spinalized animal, clonidine-induced, air stepping with no ground reaction forces).…”
Section: Discussionmentioning
confidence: 66%
“…The investigators understand the ethical principles under which the journal operates and our work complies with this animal ethics checklist. In order to maximize the scientific output of each animal, they were used in other studies to investigate different scientific questions, some of which have been published (Audet et al, 2023;Lecomte et al, 2022Lecomte et al, , 2023Mari et al, 2023;Merlet et al, 2022).…”
Section: Ethical Approvalmentioning
confidence: 99%
“…Cardiac arrest was confirmed using a stethoscope to determine the death of the animal. Spinal cords were then harvested for histological analysis (Audet et al, 2023;Lecomte et al, 2023).…”
Section: General Surgical Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Proper integration of cutaneous feedback within central neural circuits is required to execute specific motor tasks and perform necessary movement corrections. For instance, during locomotion, when the foot dorsum contacts an obstacle during the swing phase, a coordinated reflex response, termed the stumbling corrective reaction, allows the perturbed limb to step away from and over the obstacle to avoid falling, as shown in cats and humans (Forssberg et al 1977; Forssberg 1979; Frigon et al 2021; Haridas and Zehr 2003; Lecomte et al 2023; Merlet et al 2022; Prochazka et al 1978; Quevedo et al 2005a; Schillings et al 1996; Van Wezel et al 1997; Zehr et al 1997). Electrically stimulating cutaneous nerves of the foot also elicits a coordinated reflex response, consistent with the stumbling corrective reaction in cats and humans (Buford and Smith 1993; Forssberg 1979; Haridas and Zehr 2003; Lam et al 2003; Potocanac et al 2016; Prochazka et al 1978; Quevedo et al 2005a, 2005b; Schillings et al 2000, 2005; Van Wezel et al 1997; Wand et al 1980; Zehr et al 1997).…”
Section: Introductionmentioning
confidence: 99%